Penyuluhan literasi digital anti Hoax, Bullying, dan ujaran kebencian pada remaja di kota Ternate - Silvani Umar Ali; Naniek Jusnita (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2022)
The advancement and development of internet technology have resulted in an overuse of technology among urban youth. In response to the current conditions and situations, it is crucial to prevent and filter information from community observers through counseling or socialization. This is because some information can be harmful and cause a lot of harm to teenagers, which can affect their mental health and how productive they are as teenagers. Therefore, the purpose of carrying out this community service activity is to provide counseling and assistance in the form of education to the public, especially teenagers, about the intelligent and wise use of social media to avoid the misuse and dissemination of information that contains elements of hoaxes, bullying, and hate speech. This activity is conducted through counseling using lectures, discussions, and simulation methods. Participants totaled 50 people, including youth representatives from North Ternate, South Ternate, and Central Ternate. The results of this counseling activity show that teenagers in Ternate City have relatively high digital literacy skills. Not only aware of the ethics of communication but also have constructive skills in receiving, producing, and sharing informative content. Teenagers can identify social media content that contains hoaxes, bullying, and hate speech. This can be seen from partners' recognition of social media content that contains hoaxes, bullying, and utterances of hate towards smart people using social media without being involved in misusing information, and you can start from yourself. Equip participants with knowledge about hoaxes, bullying, and hate speech so they can campaign against it among family, friends, and other closest people